The immune response as a therapeutic target in non-alcoholic fatty liver disease - Ortiz-López, Nicolás; Fuenzalida, Catalina; Dufeu, María Soledad; Pinto-León, Araceli; Escobar, Alejandro; Poniachik, Jaime; Roblero, Juan Pablo; Valenzuela-Pérez, Lucía; Beltrán, Caroll J. (Frontiers in Immunology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a complex and heterogeneous disorder considered a liver-damaging manifestation of metabolic syndrome. Its prevalence has increased in the last decades due to modern-day lifestyle factors associated with overweight and obesity, making it a relevant public health problem worldwide. The clinical progression of NAFLD is associated with advanced forms of liver injury such as fibrosis, cirrhosis, and hepatocellular carcinoma (HCC). As such, diverse pharmacological strategies have been implemented over the last few years, principally focused on metabolic pathways involved in NAFLD progression. However, a variable response rate has been observed in NAFLD patients, which is explained by the interindividual heterogeneity of susceptibility to liver damage. In this scenario, it is necessary to search for different therapeutic approaches. It is worth noting that chronic low-grade inflammation constitutes a central mechanism in the pathogenesis and progression of NAFLD, associated with abnormal composition of the intestinal microbiota, increased lymphocyte activation in the intestine and immune effector mechanisms in liver. This review aims to discuss the current knowledge about the role of the immune response in NAFLD development. We have focused mainly on the impact of altered gut-liver-microbiota axis communication on immune cell activation in the intestinal mucosa and the role of subsequent lymphocyte homing to the liver in NAFLD development. We further discuss novel clinical trials that addressed the control of the liver and intestinal immune response to complement current NAFLD therapies.